Synthesis, Characterization, Optical, Thermal Behaviour And Dft Investigation Of Non-Conventional Liquid Crystals - Salwadi, Nur Fatin Liyana (2023)
Two homologues series of diimine and tetraimine compounds have been successfully prepared and characterized. Elemental analysis (CHN microanalysis), FT-IR, 1D, and 2D- NMR spectroscopic techniques were employed to elucidate the molecular structures of the synthesized compounds. The liquid crystal properties and thermal behavior of all compounds were conducted by using POM and DSC. The first series comprising of homologous V-shaped compounds (3a-3g) consist of a central phenyl core connected by two identical mesogenic units which possess the imine (C=N) and ester (COO) bonds along with the terminal alkoxy chain, (-OCnH2n+1) where n = 6-12. The shorter chain compounds (n = 6 and n = 8) were monotropic nematic phase, while the compounds with longer alkoxy chain (n = 10 and n = 12) exhibited enantiotropic nematic phase. However, compounds in the first series with the odd-membered terminal alkyl chain were found to be non-mesogenic in nature. The second series of benzidine-based oligomers possess four mesogenic arms (multi-arm liquid crystal). The symmetrical four rod like imine C=N containing units possess terminal alkoxy chains CnH2n+1 of which the n ranged from 6 to 12 (4a-4g). Upon heating the molecules containing n = 8-10 and n = 12 exhibited the endothermic peaks characteristic of the crystal-mesophase transition in addition to crystal-crystal subphases.